Resilience Amid Crisis: The Impact of COVID-19 on Older Adults in Jordan - Challenges, Interventions, and Policy Innovations - Dina (Magyar Gerontológia, 2025)
The COVID-19 pandemic was not only a global health crisis but also a profound social and humanitarian challenge. Older adults, particularly those living with chronic illnesses and limited access to healthcare, were the most severely affected.